GEODIVERSITY AND SUSTAINABLE DEVELOPMENT: GEOPARKS - A NEW CHALLENGE FOR RESEARCH AND EDUCATION IN EARTH SCIENCES - Zouros, N. (Bulletin of the Geological Society of Greece, 2010)
Recently a new initiative on Geoparks was established in Europe in close synergy with UNESCO aiming at the protection, promotion and rational management of geological landscapes and significant geosites as well as the sustainable development of their hosting territories. Geoparks are broader territories which include a number of geosites linked in a network which recognize these features as keyelements for the development of geotourism through conservation and management. Greece is characterized by a complex geological setting and evolution and was subjected to a variety of geomorphological processes, resulting in a high level of geodiversity. As a result a large number of spectacular landscapes and outstanding or unique geosites are present in the country, and they are not properly managed and protected. The Lesvos Petrified Forest Geopark, the very first Greek Geopark, already counts one decade of successful operation. In order to protect and efficiently manage the petrified forest, the Natural History Museum of the Lesvos Petrified Forest was founded in 1994 as the management body of the Lesvos Petrified Forest Geopark. Next, a management plan for geological heritage protection as well as the sustainable development of the area was carried out linking the promotion of geosites, environmental education and the development of geotourism.